2019
DOI: 10.1016/j.jhsg.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaveric Study of the Posterior Interosseous Nerve and Its Branches at the Level of the Distal Radius

Abstract: Posterior interosseous nerve (PIN) damage has been cited as a cause of wrist pain syndrome after distal radius fractures. The goal of this cadaveric study was to examine this hypothesis by looking for branches between the PIN and the periosteum of the distal radius. Methods: The PIN was dissected in 10 adult specimens (8 fresh and 2 embalmed) under Â2.5 magnification. All of the dissections started from the last motor branch of the PIN, innervating the extensor indicis proprius, and proceeded from proximal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…In Plastic Surgery 30 (2) cadaveric studies, Waters and Schwartz described the diameter of the PIN to range from 1 to 5 mm, 17 while Gregory et al found the range to be 0.6 to 1.1 mm. 25 Similarly, a study using ultrasound on live patients demonstrated the diameter of the PIN to range from 1.02 + 0.22 mm. 27 These widths are similar to our mean diameter of 1.1 mm.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In Plastic Surgery 30 (2) cadaveric studies, Waters and Schwartz described the diameter of the PIN to range from 1 to 5 mm, 17 while Gregory et al found the range to be 0.6 to 1.1 mm. 25 Similarly, a study using ultrasound on live patients demonstrated the diameter of the PIN to range from 1.02 + 0.22 mm. 27 These widths are similar to our mean diameter of 1.1 mm.…”
Section: Discussionmentioning
confidence: 97%
“…20 In contrast, several other studies found much shorter lengths of harvestable PIN. Among these, Reissis et al and Gregory et al reported mean available lengths of 3.7 cm 24 and 2.7 cm, 25 while both Jariwala et al and Das et al found mean lengths of 4.69 cm 22 and 4.71 cm. 23 A more moderate mean length of 6.2 cm was found by Elgafy and colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation